Surviving the Applewhites - Tolan, Stephanie S. (HarperTrophy, 2004)
Jake, a budding juvenile delinquent, is sent for home schooling to the arty and eccentric Applewhite family's Creative Academy, where he discovers talents and interests he never knew he had.